Mencegah Kasus Aborsi Dan Pembuangan Bayi Melalui Video Klip Lagu “Sempurnakan Hariku” Rey Mbayang (Analisis Semiotik Ferdinand De Saussure) - Nur Hikmatus Sobah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
One of the benefits of the semiotic approach is being able to examine in more detail the communication conveyed by works of art. In the current digital era, works of art can take the form of photography, videography, and so on, where these works of art can provide meaning or representation of a communication message. One of the works of art in the form of videography is video clips. One example of a video clip is a song entitled